Looking into the important issues - Abd Razak, Dzulkifli (2008)
WHAT were the chances of any leader of a country being featured on the front page of a leading newspaper in India on Nov 27, the time when Mumbai was under siege? That was the day The Times of India carried this headline: "It's war on Mumbai". Others had "Warzone: Mumbai" (New Indian Express), "Mumbai under attack" (Deccan Chronicle), "Rash of terror attacks in Mumbai" (The Hindu). The brazen "highly coordinated surprise" attack (some likened it to 911) which took place the night before was an obvious attention grabber, local and foreign, bearing in mind this was not the first time that a similar assault had taken place in the financial capital of India.